Respuesta :
Simplifying
8k + 2m = 3m + k
Reorder the terms:
8k + 2m = k + 3m
Solving
8k + 2m = k + 3m
Solving for variable 'k'.
Move all terms containing k to the left, all other terms to the right.
Add '-1k' to each side of the equation.
8k + -1k + 2m = k + -1k + 3m
Combine like terms: 8k + -1k = 7k
7k + 2m = k + -1k + 3m
Combine like terms: k + -1k = 0
7k + 2m = 0 + 3m
7k + 2m = 3m
Add '-2m' to each side of the equation.
7k + 2m + -2m = 3m + -2m
Combine like terms: 2m + -2m = 0
7k + 0 = 3m + -2m
7k = 3m + -2m
Combine like terms: 3m + -2m = 1m
7k = 1m
Divide each side by '7'.
k = 0.1428571429m
Simplifying
k = 0.1428571429m